The Effectiveness of Telemedicine in Improving Access to Healthcare: A Systematic Review - Jasmin Ambas (Penelitian dan Pengembangan Ilmu, 2024)
Telemedicine has become a promising solution for increasing access to health services, especially for underserved populations and in remote areas. This research aims to test the effectiveness of telemedicine in increasing public health access and explore its integration in strengthening health-related digital literacy. This study was conducted in the context of systematic literature research, using the PRISMA method to collect and evaluate articles from reputable international databases. The results of the literature review show that telemedicine is effective in overcoming geographic barriers and limited health infrastructure, especially during crises such as the COVID-19 pandemic. However, the challenges of policy implementation, technology infrastructure, and equality of access remain important issues that need to be addressed. On the other hand, digital literacy plays a crucial role in strengthening access to health information and informed decision making. It is hoped that the integration of telemedicine with increasing digital health literacy can increase equitable access to health. The implications of this research include providing new insights for policy makers and health practitioners in optimizing the use of telemedicine to overcome access barriers and increase digital literacy among the public.